Gambling for more: casinos as a development strategy for a shrinking Korean region. - Chung-Tong Wu; Hae-Un Rii (TPR: Town Planning Review, 2017)
A South Korean former coal mining region, Gangwon Province, faced with a severe economic downturn and rapid out-migration, chose to develop a casino to revive its economy and to stabilise its shrinking population. More than a decade on, in spite of some positives from this expansionist strategy, population decline continues with no fundamental change to the relative economic position of the region. Using information from interviews, site visits, company reports and other relevant sources, this paper examines the impacts of the casino development on the region. The paper concludes that a development strategy with a well-designed institutional structure can ensure long term flow of benefits to the region, but a successful project is insufficient to arrest economic and population decline if the key issues are of national origin. A planning paradigm that takes into account national regional strategies, institutions that ensure benefits remain in the region and locally sustainable programmes are required.